A study to determine knowledge attitude and practices of the community towards street children in lusaka district - Lyamba, Jane Sikwewa (Lusaka: University of Zambia , School of Medicine, 2002)
The aim of this study was to investigate the knowledge, attitudes and practices of the people in the commmunity towards street children. Fifty people from one residential area in lusaka urban were interviewed using a structured interview schedule.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Street children --Zambia.